2020
DOI: 10.31235/osf.io/4esf7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Working From Home and the Division of Housework and Childcare Among Dual Earner Couples During the Pandemic in the UK

Abstract: This paper examines how working from home influenced the division of childcare and housework among dual earning heterosexual couples with children in the UK during the first wave of the COVID-19 lockdown. We use unique data gathered during the peak of the UK lockdown (May-June), when many employees were required to work from home, to see whether fathers flexible working was associated with a more equitable division of housework and childcare. We found mothers were more likely to be the ones carrying out more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 44 publications
4
71
3
Order By: Relevance
“…Another social shift that will be pertinent for researchers to study over time is the increase in homeworking since the beginning of the Covid-19 pandemic. In the UK, the national lockdowns significantly increased homeworking so that it became the norm for many couples and a UK-wide survey found that fathers perceived they benefitted from flexible working regarding being able to spend more time with their children (Chung et al, 2020). Chung et al (2020) suggested that this will have long-term implications for fathers and their desire to have a better balance between work and care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another social shift that will be pertinent for researchers to study over time is the increase in homeworking since the beginning of the Covid-19 pandemic. In the UK, the national lockdowns significantly increased homeworking so that it became the norm for many couples and a UK-wide survey found that fathers perceived they benefitted from flexible working regarding being able to spend more time with their children (Chung et al, 2020). Chung et al (2020) suggested that this will have long-term implications for fathers and their desire to have a better balance between work and care.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, the national lockdowns significantly increased homeworking so that it became the norm for many couples and a UK-wide survey found that fathers perceived they benefitted from flexible working regarding being able to spend more time with their children (Chung et al, 2020). Chung et al (2020) suggested that this will have long-term implications for fathers and their desire to have a better balance between work and care. Hence, whether fathers are more involved parents because of becoming stay-at-home fathers or due to the dramatic changes in work in 2020, it is likely that we will continue to observe widespread patterns of gendered change in employment and childcare in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, they challenge the equal availability of paid work for mothers, who are expected to devote more time than fathers to housework and childcare. On the other hand, some studies (Carlson et al., 2020 ; Chung et al., 2020 ; Craig & Churchill, 2020 ; Yerkes, Andre, Besamusca, et al., 2020 ) have revealed that fathers have increased their share of childcare during lockdowns. Hence, at least in terms of dividing increased childcare responsibilities, the COVID‐19 pandemic might also have some positive consequences from the gender equality perspective.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given that the COVID-19 virus impacted the elderly and immunocompromised most severely, the importance of caregiving was illuminated on a larger scale within mainstream media [ 38 , 39 ]. At the same time, the restructuring of work meant that employers and employees were questioning the dominant paradigm and the future of work [ 40 , 41 ]. In combination, the pandemic’s “silver lining” was that it facilitated discussions of workplace programs and policies to support CEs, who were being disproportionately burdened by the pandemic.…”
Section: Discussionmentioning
confidence: 99%